2015
DOI: 10.1093/ser/mwv024
|View full text |Cite
|
Sign up to set email alerts
|

The interest ecology of financial regulation: interest group plurality in the design of financial regulatory policies

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractExisting literature has offered a variety of claims regarding why financial regulatory politics features a relative dominance of the regulated financial industry. In this article we explore the broader interest group environment in which financial industry advocacy operates. Using new data on interest group participation in financial regulatory consultations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 85 publications
(93 reference statements)
2
66
0
Order By: Relevance
“…Conceptualising 'politics as organised combat' (Hacker and Pierson, 2011), the literature on instrumental power emphasises organised interests, lobbying and regulatory capture. It shows that the financial sector's high levels of unity and organisation often bring favourable political outcomes (Pagliari and Young, 2016;Young and Pagliari, 2017). Since low issue salience and 'quiet' politics generally benefits business interests (Culpepper, 2010;Massoc, 2017;), civil society-based advocacy is most effective when it succeeds in making policy issues salient and 'noisy' -as it did, in some areas of financial policy, in the aftermath of the global financial crisis (Ziegler and Woolley, 2016;Baker and Wigan, 2017;Kastner, 2018).…”
Section: Market-based Banking and The Infrastructural Power Of Financementioning
confidence: 99%
See 1 more Smart Citation
“…Conceptualising 'politics as organised combat' (Hacker and Pierson, 2011), the literature on instrumental power emphasises organised interests, lobbying and regulatory capture. It shows that the financial sector's high levels of unity and organisation often bring favourable political outcomes (Pagliari and Young, 2016;Young and Pagliari, 2017). Since low issue salience and 'quiet' politics generally benefits business interests (Culpepper, 2010;Massoc, 2017;), civil society-based advocacy is most effective when it succeeds in making policy issues salient and 'noisy' -as it did, in some areas of financial policy, in the aftermath of the global financial crisis (Ziegler and Woolley, 2016;Baker and Wigan, 2017;Kastner, 2018).…”
Section: Market-based Banking and The Infrastructural Power Of Financementioning
confidence: 99%
“…The political economy literature emphasises two forms of political power wielded by the financial sector: instrumental power, exercised through lobbying, and structural power, which derives from the financial sector's privileged position in financialised economies (Culpepper and Reinke, 2014;Woll, 2016;Pagliari and Young, 2016). This literature has yielded important results, but its treatment of the state and of finance as two separate spheres, and of state agency as purely regulatory, is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the framework of this paper also applies to processes of legitimation that take place outside the public eye. Such legitimacy struggles require less in terms of developing an effective communicative discourse and instead puts the onus on elite actors to convince each other, a process through which the expertise and professional know-how offered by industry representatives often carries the day (Seabrooke 2014, Pagliarai andYoung 2016). One pertinent example of the power of expertise is presented by who demonstrate how the Commission together with private actors, notably financial sector lobbyists, played a central role in providing the theoretical and practical firepower for the construction of the Capital Market Union.…”
Section: Legitimacy and Ideational Powermentioning
confidence: 99%
“…The literature on "transnational advocacy networks" has recognised that successful policy engagement is not merely about participation ("being there"), and that global actors do mobilise to complex policy processes by creating "transnational advocacy networks" (Carpenter, 2007;Tomaskovic-Devey et al, 2011). And the interest group literature has shown that private sector coalitions, such as those created through lobby centres, are key to global policy environments (Pagliari & Young, 2014). But work on lobbying strategies based on professional expertise and networks is limited.…”
Section: Octopuses Arrows and Lobby Centresmentioning
confidence: 99%